1999
DOI: 10.1093/rheumatology/38.4.316
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal analysis of peripheral lymphocytes of patients before and after radiation synovectomy with samarium-153 particulate hydroxyapatite

Abstract: This study further supports the relative safety of Sm-153 PHYP compared to other radiopharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 1 publication
1
15
0
1
Order By: Relevance
“…However, past experience in patients with rheumatoid arthritis and some recent studies have shown no evidence of treatmentrelated neoplasia in patients treated with isotopes [13,24]. In another study using a radioisotope samarium-153 particulate hydroxyapatite, chromosomal analysis did not reveal any increase in scored chromosometype abnormalities; this further supports the relative safety of isotopic agents in the treatment of haemophilic arthropathy [26]. In another study using a radioisotope samarium-153 particulate hydroxyapatite, chromosomal analysis did not reveal any increase in scored chromosometype abnormalities; this further supports the relative safety of isotopic agents in the treatment of haemophilic arthropathy [26].…”
Section: Discussionmentioning
confidence: 74%
“…However, past experience in patients with rheumatoid arthritis and some recent studies have shown no evidence of treatmentrelated neoplasia in patients treated with isotopes [13,24]. In another study using a radioisotope samarium-153 particulate hydroxyapatite, chromosomal analysis did not reveal any increase in scored chromosometype abnormalities; this further supports the relative safety of isotopic agents in the treatment of haemophilic arthropathy [26]. In another study using a radioisotope samarium-153 particulate hydroxyapatite, chromosomal analysis did not reveal any increase in scored chromosometype abnormalities; this further supports the relative safety of isotopic agents in the treatment of haemophilic arthropathy [26].…”
Section: Discussionmentioning
confidence: 74%
“…O’Duffy et al . [16] studied the potential long‐term effect of radiation exposure with 90 Y and Samarium‐153 ( 153 Sm) analysing the specific chromosome‐type abnormalities in peripheral leucocytes as indicators of whole body radiation exposure. The use of 90 Y increased the aberrations up to 5 times compared with baseline levels and 153 Sm, finding no increase.…”
Section: Resultsmentioning
confidence: 99%
“…Several candidates have been proposed to replace commercially available radiocolloid formulations of yttrium-90, rhenium-186 and erbium-169. These formulations include phosphorus-32 colloid [9,10], rhenium-186 sulphide [11], samarium-153 conjugated to particulate hydroxyapatite [12,13], dysprosium-165 ferric hydroxide [14,15], holmium-166 boromacroaggregates [16,17], ytterbium-175 and lutetium-177 hydroxyapatite [18,19]. In this study, the therapeutic efficacy of yttrium-90 citrate was compared to that of phosphorus-32 and rhenium-188 colloids.…”
Section: Discussionmentioning
confidence: 99%